Runeberg Suomen kansan runoilijana - Vasenius, Valfrid, 1848-1928 (Salt Lake City, UT : Project Gutenberg, 2017)
"Runeberg Suomen kansan runoilijana" by Valfrid Vasenius is a biographical work written in the early 20th century. This book examines the life and impact of the Finnish poet Johan Ludvig Runeberg, detailing how his upbringing and character contributed to his status as a significant figure in Finnish literature. It likely covers various personal and cultural factors that influenced Runeberg's development as a poet, exploring how he became a representative voice for his nation. At the start of the work, the author reflects on Runeberg's exceptional connection to the Finnish people, proclaiming that few poets have given so much to their country while receiving such acknowledgment in return. Vasenius poses foundational questions about how a single individual can embody the collective consciousness of a nation. The opening portion delves into Runeberg's ancestry and familial background, illustrating the diverse influences that shaped his personality and worldview, such as his parents$1 (Bliterary interests and the social environment of his youth. The text sets the stage for a comprehensive exploration of Runeberg's life, emphasizing his character traits and the socio-cultural context that nurtured his poetic genius. (This is an automatically generated summary.)s
Release date is 2017-03-13
E-text prepared by Jari Koivisto
Keywords: Runeberg, Johan Ludvig, 1804-1877